Kajian Hubungan Arsitektur Pohon dan Kehadiran Burung di Kampus IPB Dramaga Bogor - AZIS, MUHAMMAD CHOIRUDDIN; BUDIARTI, TATI; WIJAYA, SYARTINILIA (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016DO - 10.24843/JAL.2016.v02.i01.p01)
ABSTRACT Study of Correlation of Tree Architecture and Birds Presence in IPB Campus Dramaga Bogor Trees play a major role for creating the landscape characteristic and also functions as a habitat for many birds. Trees has characteristic created by canopy and branches shape. The research goals were to analyze the tree diversity based on its architecture, bird species richness, trees usage level by birds, and the influence given by tree architecture to bird presence. This research was conducted by divide IPB Dramaga campus into observation plots by size 300m x 300m. Then each plot was observed the trees physic include its canopy, branches, leaf size, flower and fruit existance and birds presence on the selected trees. In this research gained 99 sample trees that divided into 24 observation plots with 25 species of birds on the sample trees. From the result of analysis seen that parameter of the trees that influence bird presence are branches shape and flower existance, with model Y = 0,566 + 2,777 X1 + 2,543 X2. From the reference and research result we knew that bird most prefered tree with vertical branch and have flower on it. From this research result also recommended some tree specieses that can attract more birds. Keywords : birds habitat, observation plots, tree preference, trees